Exchange Rate and Agricultural Sector Performance in South Africa: Time Series Analysis Approach - Thaba, Tshephi Kingsley; Nengovhela, Rudzani; Ramakgasha, Molobe Joyce (International Journal of Economics and Financial Issues, 2025)
The study investigated the intricate relationship between exchange rate fluctuations and the performance of the agricultural sector in South Africa data spanning from 1986 to 2022. Compound methodology was employed for analysis, where Johansen cointegration tests reveal the presence of long run relationship among the variables after series became stationary after first difference using Augmented Dicker Fuller. Pearson correlation matrix highlights the positive effect of real exchange rate fluctuations on the gross value of agricultural production, with agricultural exports playing a significant role in driving this relationship. Further analysis using the Fully Modified Ordinary Least Squares model confirmed a positive and statistically significant relationship between agricultural exports and the gross value of agricultural production. This suggests that policies promoting increased agricultural exports could lead to higher agricultural production values. The study recommends policymakers focus on implementing measures to stabilize and predict exchange rates, which can positively influence agricultural sector performance.